Al-Jam’u Wa Al-Taufiq dan Naskh dalam Penyelesaian Kontradiksi Hukum Islam - Nindia Oktiviana (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2023)
In this modern era, the development of the science of fiqh is very rapid. This, of course, has a correlation with the understanding of the arguments originating from the Al-Qur'an and Hadith. For example, there is a legal argument that is faced with a certain problem that will find a solution, but there are also several laws that originate from the Al-Qur'an in the same context, which actually cause different thoughts in understanding it. Therefore, when there are contradictory arguments, there are several methods to solve them. However, this paper will explain the method of solving it by means of Al-Jam'u Wa Al-Taufiq and Naskh. When there are contradictory arguments, then the solution is to collect and compromise them, so it is called Al-Jam'u Wal Al-Taufiq. Whereas when there are contradictory arguments then it is resolved by strengthening or exceeding one of the arguments from other conflicting arguments so that it can be known which argument is stronger, it is called the tarjih method.